(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article is about the common medicinal hole dalachai in the Republic, which describes the morphology, distribution, medicinal properties of the hole dalachai plant. It is also said that the hole field has been known since ancient times and was also mentioned in the works of Abu Ali ibn Sina and Abu Rayhan Beruni.